Phenoxyethanol, reproduction and development: additional studies are needed. (8th May 2020) - Garlantézec, R.; Warembourg, C.; Beranger, R.; Chevrier, C.
Abstract : Linked article: B. Dréno et al. J Eur Acad Dermatol Venereol 2020;34:e409–e410. https://doi.org/10.1111/jdv.16343 .